Elements of positive relationships among Facebook users - Ooi, Shok Hong; Intan Hashimah Mohd. Hashim (Penerbit Universiti Kebangsaan Malaysia, 2018)
Based on current literature review, there is no clear definition of positive relationships. A wide variety of concepts are used interchangeably in the literature to describe positive relationships. There are still debates as to what represent positive aspects of relationships, especially in the context of online interactions such as Facebook. As an attempt to further understand about what elements comprise positive relationships, particularly in the context of online relationships, this study examines responses from 800 participants on positive aspects of their relationships in Facebook. Participants were university students from a northern Malaysian public university (178 males; 622 females) an the age range were from 19 to 39 years old. The study was conducted online using Google Form online survey. The online survey was posted in e-learning for three months in order for students to participate in this research. From the qualitative analysis, responses can be divided into eight major themes including social support, trust, interaction, positive emotion, motivation, closeness, understanding and others. The findings shed some lights on elements of positive relationships especially in online context. It also highlights similarities between online and offline relationships. The study increases understanding on how positive aspects of relationships can be conceptualised and measured and further extend theories of positive relationships across online relationships.